A brief introduction into European Real Estate private equity funds including legal framework and empirical analysis - Süleyman, Reber (2022)
This paper uses data from Preqin to investigate whether fund strategy, fund size and domiciliation have an impact on fund’s Net-IRR in Europe. The results confirm a positive effect of Net-IRR being higher for more risky fund strategies. Looking at fund size a negative effect on Net-IRR is observed, meaning that with increasing fund size the Net-IRR of a fund decreases. This paper clearly demonstrates the association between a fund’s Net-IRR as well as factors such as: fund strategy, fund length and fund size. Moreover, the paper provides insight into the various legal frameworks, existing across Europe, as well as combing theory with real world applicability through two relevant and distinct case studies: KKR and DLE